The Concept of Social Interaction in Education: Perspectives from the Kitab Ta’lim Muta’allim - Ainiyah, Navisah Al; Muhid, Abdul (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This research aims to examine the concept of social interaction in education based on the thoughts of Sheikh Az Zarnuji in the book of Ta'lim Muta'allim.The main focus is on describing the ideal form of interaction between teachers and students, as well as between students.The method used was a literature study,which involved selecting relevant sources, in-depth reading,critical analysis of the content and identification of appropriate solutions.The collected data was then grouped thematically to facilitate the writing process. Humans are social creatures by nature, and regular interactions help socialize individuals to meet needs, overcome life's challenges and build reciprocal relationships. Positive interactions between teachers and students enhance educational goals, allowing learners to feel valued, motivated and engaged in the educational process. Islam emphasizes the importance of positive social interaction and behavior, suggesting that friendship and social engagement are essential for personal social and moral growth.Through social interaction, individuals learn to distinguish right from wrong and develop social and moral values. Education serves as the basis for instilling social values, influencing social behavior and the future of individuals.The Ta'lim Muta'allim emphasizes the importance of adab (etiquette) in education and daily life, highlighting respectful interactions between students and teachers. It remains relevant as it provides guidance on ethical behavior, respectful communication, and positive social interaction, ultimately aiming to create a whole individual with integrity and responsibility.With a focus on manners, collaborative learning, and effective communication, social interactions can foster a harmonious educational environment and aid in the development of student character and leadership.